The Development of Android Applications in Junior High Schools as Learning Media in Astronomy Course in SMP Cendekia Insani - Zainur Rasyid Ridlo; Rusdianto Rusdianto; Luthfin Afafa; Efrika Marsha Ulfa (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
This Research have a purpose to exploring teachers’ preference on development of learning media integrating assessment with android application as online assessment in science learning in SMP Cendekia Insani. Research and development use an ADDIE Model. Steps of ADDIE Model is Analysis, Design, Development, Implementation and Evaluation. Analysis is the steps description process of what is going to be taught and forms the basis of all other steps. Design is determine the process of have an information and development a strategy of analysis the problem. Development the component of multimedia are prepared during this phase. Implementation is development result is applied in learning process to know it’s the quality. Evaluation is the last step to evaluation and have a data to improve a research. This research have a result of most of the teachers prefers the online assessment that integrated with android application rather than the conventional one especially in the online learning environment nowadayas.